Investigating factors affecting fans’ intention to attend anime events: Conceptual - Mashita, Abdul Jabar; Shareenie Shera, Abdul Hamid; Zaity Akhtar, Mukhtar; Nik Rozilaini, Wan Mohamed; Shahira, Abdul Jabar; Mohd Shafiq, Abdul Jabar (AMH International, 2024)
This study proposes a conceptual framework to investigate the factors influencing anime fans' intention to attend anime events. As the popularity of Japanese animation (anime) proliferates globally, anime events have emerged as a distinct tourism market segment. However, academic research on anime event attendance factors is limited. This study aims to address this gap by developing a framework integrating three key factors frequently highlighted in the general event and fan culture literature: event image, travel motivations, and media information. Event image denotes attendees' holistic perceptions encompassing cognitive and affective dimensions. Travel motivations refer to internal and external drivers stimulating the intention to attend, such as escapism, socialization, and novelty-seeking. Media information represents sources informing attendees' perceptions and decisions through platforms like social media and websites. The framework posits that these three factors directly influence fans' intention to attend anime events. A quantitative methodology will be utilized to collect survey data from anime communities and analyse the model via PLS SEM techniques. The framework contributes a theoretical understanding of anime event attendance, validates linkages between factors, and provides practical implications for event organizers and marketers to enhance the appeal and competitiveness of anime events. Further research could extend the model’s generalizability, explore causal mechanisms between factors, examine additional variables, and conduct longitudinal studies on evolving attendee behaviour and preferences.